2021
DOI: 10.1159/000519374
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Salivary Tryptase Levels in Children following Oral Food Challenges

Abstract: <b><i>Background:</i></b> Oral food challenge (OFC) is commonly used to diagnose food allergy. This test is time and resource intensive, and conclusions are not always unequivocal as this relies on the interpretation of symptoms. Therefore, an objective marker would improve the accuracy of the diagnostic workup of food allergy. <b><i>Objectives:</i></b> The aim of this study was to investigate whether tryptase can be detected in saliva of children following OFC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recently, we found that tryptase could be detected in saliva samples (by chewing on a synthetic swab) of children that underwent an oral food challenge. 6 Here, we aimed to gain insight into the kinetics of this biomarker and we investigated if salivary histamine can also be detected, now using a different method of saliva collection (passive drooling) which is broadly used in research with salivary biomarkers and is better suitable for children.…”
Section: Investigation Of Novel Salivary Biomarkers In Paediatric Foo...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we found that tryptase could be detected in saliva samples (by chewing on a synthetic swab) of children that underwent an oral food challenge. 6 Here, we aimed to gain insight into the kinetics of this biomarker and we investigated if salivary histamine can also be detected, now using a different method of saliva collection (passive drooling) which is broadly used in research with salivary biomarkers and is better suitable for children.…”
Section: Investigation Of Novel Salivary Biomarkers In Paediatric Foo...mentioning
confidence: 99%
“…1 As described previously, both challenge days consist of a maximum of seven steps with increasing dose of allergenic protein (starting dose 3 mg, total amount 4443 mg) and 30 min waiting time between each dose. 6 During the placebo day, no food allergen was administered. Symptoms were registered using the scoring system as proposed in a recent publication by Grabenhenrich et al 7 In short, symptoms were divided into five categories (skin, respiratory, gastrointestinal, cardiologic/neurologic and other) and classified as mild, moderate and/or severe.…”
Section: Investigation Of Novel Salivary Biomarkers In Paediatric Foo...mentioning
confidence: 99%
See 1 more Smart Citation